KENDALA UNITED NATIONS CHILDREN’S FUND (UNICEF) DALAM USAHA MENGURANGI KASUS PEKERJA ANAK DI INDIA - Natasha Callista; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research analyzes how the Obstacles that faced by the United Nations Children’s Fund (UNICEF) in an Effort to reduce the number of child labor cases in India. Child labor in India has resulted in violations of the children’s Rights, and increase the risk of many kind violence, exploitation and discrimination. UNICEF as an international organizations dealing with child problems in the World is making efforts to reduce the number of the child laborers in India. The efforts are being made through programs to improve education for children in India, providing shelter and material assistance and participating in efforts to amend the Child Labor Law in India. Efforts are being made to reduce the number and solve the problem of child labor in India.This research uses qualitative methods, with data collection techniques through literature studies sourced from several books, journals, articles, web sites. This study uses the perspective of Pluralism, the theory of the role of International Organizations.The results of this paper indicate that UNICEF has not been able to act as the main actor in solving the problem of child labor in India, due to obstacles that came from internal or external factors which is assessed from three aspects, Social and Economic Conditions, Ambiguity, and Limited Capacity of UNICEF. Keywords: Obstacles, Child labor, India.